Language Analysis of Sexism in Online Gender-Based Violence (KGBO) on Facebook Platform Reels in 2023 - Ma’rifah Nurmala; Sari Wulandari; Hairuddin Cikka (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Online gender based violence (KGB Online) or sexual violence facilitated by technology, just like real world gender-based violence, the act of violence requires the deliberate intention of harassing the victim based on gender or sexuality. The Ministry of Women's Empowerment and Child Protection (KemenPPPA) revealed that 8.7% of women from 15 to 64 years old have experienced online sexual harassment. In fact, as many as 3.3% of women experienced it in the past year. This figure is based on the 2021 national women's life experience survey conducted by KemenPPPA and BPS. The previous studies results showed that social media gave birth to a new form of harassment that places women as objects due to the dominance of power built by patriarchal culture and has an impact on other forms of harassment such as malicious comments, hate speech, indecent image content and online harassment. This study was aimed at examining the language of sexism in the form of online gender-based violence (KGB Online) sourced from netizen comments on the reels platform on Facebook. Data collection was taken randomly using a qualitative approach with a document study method. Based on the results and conclusions, the language of sexism has a negative impact, which is mentally bad and degrading negative body image in general.